Greater involvement of HIV-infected peer-mothers in provision of reproductive health services as "family planning champions" increases referrals and uptake of family planning among HIV-infected mothers - Peter Mudiope; Ezra Musingye; Carolyne Onyango Makumbi; Danstan Bagenda; Jaco Homsy; Mai Nakitende; Mike Mubiru; Linda Barlow Mosha; Mike Kagawa; Zikulah Namukwaya; Mary Glenn Fowler (BMC, 2017)
Abstract Background In 2012, Makerere University Johns - Hopkins University, and Mulago National Referral Hospital, with support from the National Institute of Health (under Grant number: NOT AI-01-023) undertook operational research at Mulago National Hospital PMTCT/PNC clinics. The study employed Peer Family Planning Champions to offer health education, counselling, and triage aimed at increasing the identification, referral and family planning (FP) uptake among HIV positive mothers attending the clinic. Methods The Peer Champion Intervention to improve FP uptake was introduced into Mulago Hospital PMTCT/PNC clinic, Kampala Uganda. During the intervention period, peers provided additional FP counselling and education; assisted in identification and referral of HIV Positive mothers in need of FP services; and accompanied referred mothers to FP clinics. We compiled and compared the average proportions of mothers in need that were referred and took up FP in the pre-intervention (3 months), intervention (6 months), and post-intervention(3 months) periods using interrupted time series with segmented regression models with an autoregressive term of one. Results Overall, during the intervention, the proportion of referred mothers in need of FP increased by 30.4 percentage points (P < 0.001), from 52.7 to 83.2 percentage points. FP uptake among mothers in need increased by over 31 percentage points (P < 0.001) from 47.2 to 78.5 percentage points during the intervention. There was a positive non-significant change in the weekly trend of referral β3 = 2.9 percentage points (P = 0.077) and uptake β3 = 1.9 percentage points (P = 0.176) during the intervention as compared to the pre-intervention but this was reversed during the post intervention. Over 57% (2494) mothers took up Depo-Provera injectable-FP method during the study. Conclusions To support overstrained health care work force in post-natal clinics, peers in trained effective family planning can be a valuable addition to clinic staff in limited-resource settings. The study provides additional evidence on the utilization of peer mothers in HIV care, improves health services uptake including family planning which is a common practice in many donor supported programs. It also provides evidence that may be used to advocate for policy revisions in low-income countries to include peers as support staff especially in busy clinic settings with poor services uptake.